PREPARATION OF 1,2,3 –TRIAZOLE LINKED PIPERAZINE AND IMIDAZOLE DERIVATIVES VIA CLICK CHEMISTRY - Ruaa Jameel Kamel (European Science Publishing, 2024)
An efficient method has been developed for the synthesis of 1,2.3–triazoI–Iinked piperazine, imidazole ring, through azid–alkyne using click chemistry. one of pair of chemical compounds known as piperazine, imidazole and triazoles of hetero compounds are profoundly receptive and are known to possess potent diverse actives liked analgesic, anti–HIV, anti–cancer, anti– bacterial and other. In conclusion numerous biological actions of 1,2,3–triazole derivative of heterocyclic compounds.
Keywords: click chemistry, piperazine, imidazole, 1,2,3―triazoIe.